[CrF(O2CtBu)2]9: Synthesis and Characterization of a Regular Homometallic Ring with an Odd Number of Metal Centers and Electrons. Issue 31 (13th June 2016) - Woolfson, Robert J.; Timco, Grigore A.; Chiesa, Alessandro; Vitorica‐Yrezabal, Inigo J.; Tuna, Floriana; Guidi, Tatiana; Pavarini, Eva; Santini, Paolo; Carretta, Stefano; Winpenny, Richard E. P.
Abstract: The first regular homometallic ring containing an odd number of metal centers is reported. The ring was synthesized by means of amine‐templated self‐assembly. Extensive physical characterization studies, including magnetic measurements, powder inelastic neutron scattering (INS), and DFT calculations, show that the molecule has a near perfect match to the expected behavior for a frustrated system with the lowest energy pair of S =1/2 spin states separated by only 0.1 meV (0.8 cm −1 ). Abstract : Spin frustration : The first homometallic wheel compound containing an odd number of metal centers and an odd number of electrons has been synthesized. The extent of spin frustration in the ring has been characterized spectroscopically, showing a near perfect frustrated ground state from a sterically undemanding chemical structure.